The Effect of TGT and TGfU Learning Models on Improving Short Distance Running Psychomotor Learning Outcomes - Pramuji, Ramdani; Pandu Kresnapati; Galih Dwi Pradipta (UNIB Press, 2026)
This study aims to determine the effect of the Teams Games Tournament (TGT) and Teaching Games for Understanding (TGfU) learning models on improving short-distance running psychomotor learning outcomes in class VIII students of SMP Negeri 7 Semarang. The study used a quantitative approach with an experimental method through a Two Group Pretest–Posttest Design. The research sample consisted of 63 students divided into two groups, namely class VIII A who were given the TGT learning model treatment and class VIII B who were given the TGfU learning model treatment. The research instrument was a short-distance running skills test that assessed aspects of the initial attitude (start), implementation, and final attitude (finish). Data analysis was carried out using normality tests, homogeneity tests, and t-tests. The results of the study showed that both learning models had a significant effect on improving psychomotor learning outcomes in short-distance running. The TGT learning model experienced an average increase of 22.3%, while the TGfU learning model experienced an increase of 21.7%. The t-test results showed a significance value of p < 0.05, which indicated that there were differences in learning outcomes before and after treatment in each learning model. Based on the percentage increase and the results of statistical tests, the TGT learning model was declared more effective than TGfU in improving psychomotor learning outcomes in short-distance running. Thus, both learning models can be used as alternatives for PJOK learning, with the TGT model being more recommended for improving students' psychomotor skills in short-distance running material.